Pengaruh Keragaman Barang Dagangan dan Kepuasan Pembeli Terhadap Tingkat Pembelian Barang di Toko Online - Budiono, Anshori; Mulyani, Sri; Fauzi Ramdani, Alfi; Candra, Dedi; Hutauruk, Hardi (Jurnal Etnik: Ekonomi-Teknik, 2022)
Increasingly sophisticated digital technology has changed the supply and demand patterns of economic actors through e-commerce or digital marketing. The ease of opening an online store on the marketplace has grown the number of sellers on the marketplace in Indonesia, thereby increasing the level of competition among online stores. With increasingly fierce business competition in the marketplace, sellers at online stores must be able to determine the right sales strategy, one of which is to determine the diversity of merchandise in online stores. This study was conducted to determine the effect of merchandise diversity and buyer satisfaction on the level of purchases at online stores by analyzing data on purchasing goods and consumer ratings in the Shopee Indonesia marketplace. The independent variable in this study is the diversity of merchandise in the online store and the level of buyer satisfaction in the form of a five-star rating by the buyer for purchasing goods at the online store. Meanwhile, the response variable is the level of purchases of goods per year at the online store. From the data analysis, it can be concluded that the diversity of merchandise has an insignificant effect on the level of purchasing goods. Meanwhile, buyer satisfaction has a strong significant influence on the level of purchase of goods